A Critical Analysis of the Macroeconomic Policies in Brazil from Lula da Silva to Dilma Rousseff (2003-2014) - de Paula, Luiz Fernando; Ferrari, Fernando (Brazilian Keynesian Review, 2015)
<span style="line-height: 115%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-font-kerning: 16.0pt; mso-ansi-language: EN-US; mso-fareast-language: X-NONE; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">In this short article, we aim at presenting a critical analysis of the macroeconomic policies implemented by the Lula da Silva and Dilma Rousseff governments in Brazil. The main hypothesis is that the economic framework of the ‘leftist’ governments has been managed pragmatically, mainly due to the <span style="line-height: 115%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA;" lang="EN-US">global financial crisis (GFC) and the Great Recession (GR)<span style="line-height: 115%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-font-kerning: 16.0pt; mso-ansi-language: EN-US; mso-fareast-language: X-NONE; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">, and is still conservative, and cannot be considered as genuine Keynesian policies.